2022
DOI: 10.1021/jacs.2c07994
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Kinetics of HO2 Reactions with Aldehydes in the Atmosphere: High-Order Dynamic Correlation, Anharmonicity, and Falloff Effects Are All Important

Abstract: Kinetics provides the fundamental parameters for elucidating sources and sinks of key atmospheric species and for atmospheric modeling more generally. Obtaining quantitative kinetics in the laboratory for the full range of atmospheric temperatures and pressures is quite difficult. Here, we use computational chemistry to obtain quantitative rate constants for the reactions of HO 2 with HCHO, CH 3 CHO, and CF 3 CHO. First, we calculate the high-pressure-limit rate constants by using a duallevel strategy that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 78 publications
3
23
0
Order By: Relevance
“…We see that the SRP scaling factor differs from the standard CCSD­(T)-F12a/cc-pVDZ-F12 scaling factor by 0.007 or more for four of the cases including both transition states as well as SO 3 and water dimer. This shows the need for specific treatment of the anharmonicity at some of the stationary points, in keeping with previous investigations that showed that standard scale factors are less accurate for some transition states, ,, although the standard scale factors are good for most stable molecules and some transition states. , The table shows that the SRP anharmonic ZPEs at the transition states differ from standard-scaling-factor anharmonic ZPEs by 0.43 and 0.51 kcal mol –1 and from directly calculated harmonic ZPEs by 1.09 and 1.17 kcal mol –1 .…”
Section: Methods For Electronic Structuresupporting
confidence: 84%
See 1 more Smart Citation
“…We see that the SRP scaling factor differs from the standard CCSD­(T)-F12a/cc-pVDZ-F12 scaling factor by 0.007 or more for four of the cases including both transition states as well as SO 3 and water dimer. This shows the need for specific treatment of the anharmonicity at some of the stationary points, in keeping with previous investigations that showed that standard scale factors are less accurate for some transition states, ,, although the standard scale factors are good for most stable molecules and some transition states. , The table shows that the SRP anharmonic ZPEs at the transition states differ from standard-scaling-factor anharmonic ZPEs by 0.43 and 0.51 kcal mol –1 and from directly calculated harmonic ZPEs by 1.09 and 1.17 kcal mol –1 .…”
Section: Methods For Electronic Structuresupporting
confidence: 84%
“…Two kinds of vibrational-frequency scale factors were used. For the LL calculations and calculations used to check convergence, we used standard scale factors given in Table S1 (tables with a prefix S are in the Supporting Information), and for HL calculations, we used specific reaction-parameter scale factors , given in Tables S2 and . Standard scale factors take the form λ ZPE = λ Anh λ normalH where λ H corrects a specific combination of method (wave function method or density functional) and basis set for its systematic error in the prediction of harmonic frequencies (and hence also in the prediction of harmonic ZPEs), and λ Anh , which is independent of method and basis set, is a general parameter (equal to 0.986) for the ratio of anharmonic ZPE to the harmonic one.…”
Section: Methods For Electronic Structurementioning
confidence: 99%
“…The main sink pathway of acetaldehyde is its reaction with OH with an atmospheric lifetime of about one day. 37,85 To further investigate the important atmospheric contribution of the H 2 SO 4 + (CH 3 ) 2 NH + CH 3 CHO reaction, we compared the H 2 SO 4 + (CH 3 ) 2 NH + CH 3 CHO reaction with CH 3 CHO + OH. The rate ratio is expressed in eqn (4):where k CH 3 CHO+OH is the experimental rate constant of the CH 3 CHO + OH reaction at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“… 50 Thus, it is very difficult to determine whether HCHO + HNO 3 can occur more feasibly than HCHO + HCOOH, as the error bars are produced at the two different theoretical methods and their energy barriers are very close to each other. However, the energy barrier of HCHO + HNO 3 (8.80 kcal/mol) is much higher (at least 5 kcal/mol) than those of the HCHO + H 2 SO 4 reaction (3.5–6.1 kcal/mol) at the W2X//QCISD/cc-pV(T + d)Z level, 52 the HCHO + OH reaction (−0.12 kcal/mol) at the CCSD(T)/aug-cc-pVTZ level, 56 the HCHO + HO 2 reaction (−1.03 kcal/mol) at the MW3X-L//CCSD(T)-F12a/cc-pVTZ-F12 level, 57 the HCHO + CH 2 OO reaction (−5.26 kcal/mol) at the W3X-L//CCSD(T)-F12a/cc-pVTZ-F12 level, 40 and the HCHO + HIO 3 reaction (2.96 kcal/mol) at the CCSD(T)-F12a/def2-TZVPP//M06-2X/aug-cc-pVTZ-PP level. 58 It is noted that these reactions mentioned above were carried out using different theoretical methods; this can cause some different error bars for different theoretical methods.…”
Section: Resultsmentioning
confidence: 99%